2021
DOI: 10.1177/2325967121998050
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Contact Stress Distribution Pattern of the Patellofemoral Joint After Medial Open-Wedge High Tibial Osteotomy: An Evaluation Using Computed Tomography Osteoabsorptiometry

Abstract: Background: Medial open-wedge high tibial osteotomy (OWHTO) theoretically causes distalization and lateralization of the tibial tuberosity and the patella. Purpose/Hypothesis: The purpose of the study was to identify any changes in the stress distribution of subchondral bone density across the patellofemoral (PF) joint before and after OWHTO through the use of computed tomography (CT) osteoabsorptiometry. We hypothesized that OWHTO would alter the distribution of contact stress in the PF joint. Study Design: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Some other radiologic and biomechanical studies indicated an increase of PF contact pressure and the progression of PF OA after OW-HTO. 10,19,39 Kameda et al 31 also cited a statistically significant decrease in patellar height and degradation of the PF cartilage after OW-HTO. Using the computed tomography–osteoabsorptiometry method, their study demonstrated that the OW-HTO procedure significantly increased the stress distribution patterns of the femoral lateral trochlea and the medial portion of the patellar lateral facet.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Some other radiologic and biomechanical studies indicated an increase of PF contact pressure and the progression of PF OA after OW-HTO. 10,19,39 Kameda et al 31 also cited a statistically significant decrease in patellar height and degradation of the PF cartilage after OW-HTO. Using the computed tomography–osteoabsorptiometry method, their study demonstrated that the OW-HTO procedure significantly increased the stress distribution patterns of the femoral lateral trochlea and the medial portion of the patellar lateral facet.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review and meta-analysis revealed that the tilting angle was significantly decreased but the lateral shift ratio did not differ significantly after OW-HTO. 38 Kameda et al 31 suggested that the medial tilt of the patella occurred because of lateral and distal shifts of the tibial tuberosity forcing up the lateral side of the femur and patella. In the present study, the tilting angle and lateral shift ratio after OW-HTO were similar to those in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, OWHTO still has its shortcomings. OWHTO has been reported to have a negative effect on the patellofemoral joint postoperatively due to a decrease in patellar height (PH) and an increase in patellofemoral contact pressure 5 , 6 , 7 . Biomechanical studies indicated that the alteration in sagittal patellar height can be attributed to distalization of the tibial tuberosity following OWHTO, which leads to the patella being pulled down toward the joint lines 8 .…”
Section: Introductionmentioning
confidence: 99%